Tunjuk Ajar Melayu dalam Nyanyi Panjang Balam Ponganjuw Susunan Herman Maskar - Sabna Fitri Aulan Dari; Sudirman Shomary (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
In Pelalawan Regency, Riau, there are various types of oral literature, including Nyanyi Panjang, which contains Malay teaching instructions. The reason for this research is to obtain the Malay teaching instructions contained in the Nyanyi Panjang Balam Ponganjuw composition by Herman Maskar and to add insight into oral literature in the Malay area. The problem is how to teach Malay in the long song Balam Ponganjuw composed of Herman Maskar?. The type of research used is library research or library research. The source of the data used is the book Nyanyi Panjang Balam Ponganjuw composed of Herman Maskar. Data were analyzed by the descriptive analysis method. The theory used is Tennas Effendy (2004). Based on the data analysis, it was concluded that there were 27 Malay teaching data in the Nyanyi Panjang Balam Ponganjuw composition of Herman Maskar, namely: devotion to God Almighty as much as 4 data, Obedience to Mother and Father as much as 3 data, Obedience to the Leader as much as 2 data, Justice and Truth as much as 2 data, Trust as much as 3 data, Courage as much as 3 data, Humble nature as much as 3 data, Compassion as much as 3 data, Rights and Possessions as much as 2 data, and Thinking well of others as much as 2 data. One of the most dominant examples of Malay teaching is the aspect of piety to God Almighty because piety to God Almighty is the core of aqidah which is related to asking by praying and putting your trust in Him.